Mice lacking paternal expression of imprinted Grb10 are risk‐takers. (22nd June 2020) - Dent, Claire L.; Rienecker, Kira D. A.; Ward, Andrew; Wilkins, Jon F.; Humby, Trevor; Isles, Anthony R.
Abstract: The imprinted genes Grb10 and Nesp influence impulsive behavior on a delay discounting task in an opposite manner. A recently developed theory suggests that this pattern of behavior may be representative of predicted effects of imprinted genes on tolerance to risk. Here we examine whether mice lacking paternal expression of Grb10 show abnormal behavior across a number of measures indicative of risk‐taking. Although Grb10 +/p mice show no difference from wild type (WT) littermates in their willingness to explore a novel environment, their behavior on an explicit test of risk‐taking, namely the Predator Odor Risk‐Taking task, is indicative of an increased willingness to take risks. Follow‐up tests suggest that this risk‐taking is not simply because of a general decrease in fear, or a general increase in motivation for a food reward, but reflects a change in the trade‐off between cost and reward. These data, coupled with previous work on the impulsive behavior of Grb10 +/p mice in the delayed reinforcement task, and taken together with our work on mice lacking maternal Nesp, suggest that maternally and paternally expressed imprinted genes oppositely influence risk‐taking behavior as predicted. Abstract : Mice lacking paternal imprinted Grb10 show greater risk‐taking behavior.